POTRET PERAN KELUARGA, SEKOLAH, DAN MASYARAKAT DALAM MENANAMKAN NILAI PENDIDIKAN AKHLAK PADA PESERTA DIDIK - Halimatun Syakdiah, Yulia Warda (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2021)
The main point for the whole education activity is how leading students, whereas this process is able to prove on them, as well negative value will be null. This study state that moral education is very important thing for them. Furthermore it is necessary due to the academically term; firstly, school, and society itself. To regard moral education teachers are able to apply dialogue method. Secondly, that action proved to connect education and teaching process, thirdly; that actions have to support by the whole scopes. As well that action occur the really effort to create honesty and mandate for existing the religion space.